Ahl al-kitab Dalam Literatur Al-Quran - Rizhy Firmansyah (LP2M Universitas PTIQ Jakarta, 2017)
The evolving nature of human life demands various reforms including in the interpretation of ahl al-kitab. There are four main views of the scholars concerning the understanding of ahl al-kitab. The different views in the author's analysis are not caused by idiological factors, but rather caused by the textualisation of methodology applied in interpreting verses of the Qur'an. This article tries to blend in between texts and contexts in interpreting ahl al-Kitab so as to create objective and neutral views.